Comparison of game characteristics of male and female tennis players at grand-slam tournaments in 2016 - Carboch, J. (Trends in Sport Sciences, 2017)
The aim of our study is to compare selected game characteristics on different surfaces among all grand-slam tournaments and between male and female professional tennis players. We analyzed match characteristics from all grand-slam tournaments - Australian Open, French Open, Wimbledon and US Open. We had data from all the matches and tournaments (127 singles matches from male and 127 female singles matches per each tournament). We compared the tournaments and also the genders. The data of the match characteristics were obtained through the official tournaments websites. The results showed women won significantly more return games compared to men (by 12%); men won significantly more points after 1st and 2nd serve compared to women (by 7% or 6% respectively); men played significantly more games per set; and women played significantly more points per game. Faster surface provides greater advantage to the server. Therefore it is important to practice serves prior these tournament. The least percentage of winners was reached at US Open. The mean percentage of 2nd serve points won in women`s matches reached only 45%, therefore receiving the 2nd serve could be an advantage in women`s tennis. The receiver should use this advantage by a good return.